A study on the microscopic mechanism of methanesulfonic acid-promoted binary nucleation of sulfuric acid and water. (October 2018) - Wen, Hui; Huang, Teng; Wang, Chun-Yu; Peng, Xiu-Qiu; Jiang, Shuai; Liu, Yi-Rong; Huang, Wei
Abstract: Methanesulfonic acid (MSA) is believed to play an important role in the formation and growth of atmospheric organic aerosols and could facilitate the binary nucleation of sulfuric acid (SA)–water (W). However, understanding of larger clusters formed by gas-phase MSA with atmospheric nucleation precursors from microscopic aspect is lacking. In this work, to study the microscopic mechanism of the ternary nucleation, the structural characteristics and thermodynamics of MSA clusters with SA in the presence of up to six W molecules have been investigated. It was found that MSA forms relatively stable clusters with SA and W molecules and that acid dissociation plays an important role. The analysis of the atmospheric relevance indicates that the heterodimer MSA–SA and monohydrated cluster MSA–SA–W1 show an obvious relative concentration in the atmosphere, and thus, these species likely participate in new particle formation (NPF). However, with an increasing number of W molecules, the concentration of clusters gradually decreases. Additionally, the minimum energy isomer of MSA–SA–W4 is predicted to possess a relatively stable configuration under the employed temperature dependence analysis, and evaporation rate analysis. The detailed non-covalent interactions of MSA-SA-Wn, n = 3–6 cluster have been thoroughly studied for the first time. Highlights: The interaction of MSA with SA in presence of water has been investigated. The results indicate that MSA could forms clusters with SA in the atmosphere. The heterodimer and monohydrated clusters are more favorable in real conditions. First kinetic investigation to MSA-SA-Wn clusters has been evaluated. Non-covalent interactions of the minimum energy isomers are investigated.